Pemberdayaan Kader Posyandu untuk Meningkatkan Kemampuan Deteksi Dini dan Stimulasi Perkembangan Anak Usia Dini di Indonesia - Sofie Handajany; Emmi Wahyuni; Lutfiasih Rahmawati; Lisnadiyanti Lisnadiyanti; Hayyu Naafi Hidhayanti; Nur Khotimah Elfiyani; Edi Gunawan; Dyas Nurvitasari Puspita; Khansa Aulia Putri; Harmoko Harmoko; Henny Listyawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Several toddlers in Indonesia face developmental challenges, including delays in fine and gross motor skills, hearing impairments, speech delays, and cognitive issues. One of the main factors contributing to these problems is the limited ability of families to provide the proper stimulation needed for child development. In this context, the role of Pos Pelayanan Terpadu (Posyandu) cadres becomes essential. Cadres with good skills, high motivation, and consistent enthusiasm are needed to support the success of the Posyandu program, especially in early childhood developmental screening. This community service activity was designed to provide basic training for Posyandu cadres, with a primary focus on enhancing their ability to stimulate and detect early signs of developmental delays in children. The training was held on May 4, 2025, at the Mu'thi Jaya Indonesia Foundation Meeting Room and attended by 30 Posyandu cadres. An evaluation was conducted using pre- and post-test questionnaires to assess the knowledge and skills of the participants before and after the training. The evaluation results showed a significant improvement in the cadres' knowledge and skills related to early detection and stimulation of child development. Data analysis revealed a p-value of 0.074, indicating a substantial increase in understanding after the training. However, continuous support is necessary to ensure that early detection practices and child stimulation continue to be implemented effectively in the field. Routine monitoring and evaluation are also crucial to assess the long-term impact of this program on children's development in the community, as well as to ensure that the Posyandu program continues to function effectively in supporting the growth and development of children, particularly during the critical early years of life.